Bulbophyllum lingii, a new species (Malaxideae, Epidedroideae, Orchidaceae) from Hainan, China - Huang, Ming-Zhong; Yang, Guang-Sui; Lan, Si-Ren; Yin, Jun-Mei (Phytotaxa, 2020)
A new species, Bulbophyllum lingii (Orchidaceae: Epidedroideae: Malaxideae) from Hainan, China, is described and illustrated. Detailed morphological comparisons indicate that B. lingii is similar to B. catenarium, but differs in having oblong petals, lip margins from base of side-lobes to lip tip recurved, adaxial surface of top part glabrous, stigma with a rather distinct basal callus, foot with about 1/3 free part. The conservation status of B. lingii is assessed and taxonomic notes are provided.